Latest beam test results from ATF2 with the font ILC prototype intra-train beam feedback systems - Apsimon, R; Bett, D; Burrows, P; Christian, G; Constance, B; Dabiri Khah, H; Perry, C; Resta Lopez, J; Swinson, C (2010)
We present the design and beam test results of a prototype beam-based digital feedback system for the Interaction Point of the International Linear Collider. A custom analogue front-end signal processor, FPGA-based digital signal processing boards, and kicker drive amplifier have been designed, built, deployed and tested with beam in the extraction line of the KEK Accelerator Test Facility (ATF2). The system was used to provide orbit correction to the train of bunches extracted from the ATF damping ring. The latency was measured to be approximately 140 ns.